Similarity in Diet Quality Between Children or Adolescents With Obesity and Their Mothers - Hangsook Lee; Jieun Kim; Nayoung Kim; Hyung Gyu Park; Yoon Myung Kim; Kyung Hee Park; Hyunjung Lim (Clinical nutrition research, 2025)
Obesity is a multifactorial chronic disease influenced by behavioral, environmental, genetic, and psychological factors. One primary determinant of childhood obesity is the presence of dietary factors commonly acquired through the shared home food environment, which parents can greatly influence. Thus, the present study examined the similarity in diet quality between children or adolescents with obesity and their mothers. We analyzed baseline data collected from the Intervention for Children and Adolescent obesity via Activity and Nutrition study. Seventy mother-offspring dyads were identified, which included children and adolescents with obesity aged 8-16 years and their mothers living in Seoul and Gyeonggi Province, South Korea. Food or nutrient intake and diet quality were evaluated from 3-day food records. Childhood obesity was defined as body mass index ≥ 95th percentile based on the 2007 Korean National Growth Charts. No significant difference was observed in the diet quality score between children with obesity and their mothers. However, correlation coefficients between mothers and their children’s total Diet Quality Index-International (DQI-I) score (r = 0.30) and subcategories, such as variety (r = 0.29), adequacy (r = 0.43), moderation (r = 0.45), and overall balance (r = 0.30), were positively correlated (p < 0.05). Linear regression analysis of the influence of maternal diet quality on offspring diet quality revealed that the maternal DQI-I score influenced the offspring’s DQI-I score, consistent with our prediction. Further studies with larger and more representative samples are needed to confirm the applicability of our findings to all children and adolescent populations.